Pharmacy Integrated Transitions (PIT) trial: a protocol for a pragmatic cluster-randomised crossover trial - Elizabeth Austin; Catherine Kim; Elizabeth J Austin; Giana H Davidson; Bryan A Comstock; Sarah E Monsell; Bryan Comstock; Mariam N Hantouli; Jocelyn Chaing; Arzu Ahmed Dervish; Nick J Gionet; Shalynn Howard; et al. (BMJ Open)
Introduction Ineffective coordination during care transitions from hospitals to skilled nursing facilities (SNFs) costs Medicare US$2.8–US$3.4 billion annually and results in avoidable adverse events. Approximately 70% of patients experience medication errors during these transitions, resulting in downstream consequences such as medication-related problems and unplanned readmissions. Patients and caregivers report significant emotional distress and concerns, particularly regarding medication management. Current protocols often fail to ensure effective medication management and communication between hospital and SNF teams. Developed with input from multiple interest holders, the Pharmacy Integrated Transitions (PIT) programme enhances these transitions by improving medication safety and communication. The programme includes a pharmacist who reconciles patients’ medications during transitions from hospitals to SNFs, and a structured handoff between hospital and SNF clinical teams. A rigorous, pragmatic trial is needed to assess the programme’s effectiveness in enhancing care transitions compared with standard practices.The PIT trial aims to evaluate the effectiveness of the PIT programme in improving patients’ care transitions from hospitals to SNFs compared with usual care, and to characterise multiple interest holders’ perspectives on its implementation fidelity, effectiveness and needed support for sustainment.Methods and analysis The PIT trial is a parallel cluster-randomised controlled crossover trial design, with randomisation occurring at the SNF cluster level. The trial is conducted across 4 hospitals and 14 independent SNFs in Washington State. SNFs are stratified by patient volume before being randomly assigned to either the PIT programme or usual care. The trial aims to include a diverse patient population transitioning from hospitals to SNFs. The primary outcome is medication-related problems within 30 days posthospital discharge. Clinical adverse events, readmission rates and emergency department visits will be compared. Additionally, we will conduct a mixed-methods summative evaluation to assess multiple interest holders’ perspectives on the PIT programme’s implementation fidelity, effectiveness and the support required for its sustainment.Ethics and dissemination This trial was approved by the University of Washington’s Human Subjects Division on 9 September 2020 (STUDY00011018_PIT). The trial was reviewed by the University of Washington Institutional Review Board (IRB) and was issued a waiver of consent. The University of Washington serves as the IRB for all 14 of the Post Acute Care Skilled Nursing Facility study sites. Results from this trial will be published in peer-reviewed journals. Results may also be presented at international conferences.Trial registration number NCT05241951.